VARIABILITY IN SECOND LANGUAGE LEARNING: The Roles of Individual Differences, Learning Conditions, and Linguistic Complexity. Issue 2 (18th May 2016) - Tagarelli, Kaitlyn M.; Ruiz, Simón; Vega, José Luis Moreno; Rebuschat, Patrick
Abstract : Second language learning outcomes are highly variable, due to a variety of factors, including individual differences, exposure conditions, and linguistic complexity. However, exactly how these factors interact to influence language learning is unknown. This article examines the relationship between these three variables in language learners. Native English speakers were exposed to an artificial language containing three sentence patterns of varying linguistic complexity. They were randomly assigned to two groups—incidental and instructed—designed to promote the acquisition of implicit and explicit knowledge, respectively. Learning was assessed with a grammaticality judgment task, and subjective measures of awareness were used to measure whether exposure had resulted in implicit or explicit knowledge. Participants also completed cognitive tests. Awareness measures demonstrated that learners in the incidental group relied more on implicit knowledge, whereas learners in the instructed group relied more on explicit knowledge. Overall, exposure condition was the most significant predictor of performance on the grammaticality judgment task, with learners in the instructed group outperforming those in the incidental group. Performance on a procedural learning task accounted for additional variance. When outcomes were analyzed according to linguistic complexity, exposure condition was the most significant predictor for two syntactic patterns, but it was not a predictor for the most complex sentence group; instead, procedural learning ability was.